John Evans diary notes - Evans, John, active 1708-1714
Volume (10 pages) of diary notes.
Army officer and trader, pf Virginia.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Army officers; Traders